2012
DOI: 10.1371/journal.pone.0051466
|View full text |Cite
|
Sign up to set email alerts
|

Nullbasic, a Potent Anti-HIV Tat Mutant, Induces CRM1-Dependent Disruption of HIV Rev Trafficking

Abstract: Nullbasic, a mutant of the HIV-1 Tat protein, has anti-HIV-1 activity through mechanisms that include inhibition of Rev function and redistribution of the HIV-1 Rev protein from the nucleolus to the nucleoplasm and cytoplasm. Here we investigate the mechanism of this effect for the first time, establishing that redistribution of Rev by Nullbasic is not due to direct interaction between the two proteins. Rather, Nullbasic affects subcellular localization of cellular proteins that regulate Rev trafficking. In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 48 publications
4
54
0
Order By: Relevance
“…As expected, the localization of MYC-Rev expressed alone was predominantly nucleolar of Nullbasic-mCherry and MYC-Rev had no apparent effect on DDX3 and DDX17 subcellular distribution [see Additional file 3]. As previous observed [35,37], coexpression of Nullbasic-mCherry with MYC -Rev induced Rev mislocalization from the nucleolus to the nucleoplasm and cytoplasm ( Figure 4A, row 4). These data thus show that Nullbasic associates with DDX1 leading to the alteration of DDX1 subcellular distribution.…”
Section: Nullbasic Affects the Subcellular Distribution Of Ddx1supporting
confidence: 79%
See 4 more Smart Citations
“…As expected, the localization of MYC-Rev expressed alone was predominantly nucleolar of Nullbasic-mCherry and MYC-Rev had no apparent effect on DDX3 and DDX17 subcellular distribution [see Additional file 3]. As previous observed [35,37], coexpression of Nullbasic-mCherry with MYC -Rev induced Rev mislocalization from the nucleolus to the nucleoplasm and cytoplasm ( Figure 4A, row 4). These data thus show that Nullbasic associates with DDX1 leading to the alteration of DDX1 subcellular distribution.…”
Section: Nullbasic Affects the Subcellular Distribution Of Ddx1supporting
confidence: 79%
“…In this study, we focused on nuclear Nullbasic interactors as our previous studies indicated that Nullbasic disrupted the nucleolar colocalization of HIV-1 Rev with CRM1, B23 and C23 but did not affect importin β-and transportin 1-mediated Rev nuclear import pathways [37], suggesting that Nullbasic interferes with specific components of a Rev nuclear complex. The experimental strategy used to identify protein complexes associated with Nullbasic is illustrated in Figure 1A.…”
Section: Identification Of Nullbasic Interacting Proteins By Lc Ms/msmentioning
confidence: 99%
See 3 more Smart Citations